Pengaruh Penggunaan Transaksi Digital di Berbagai E-commerce Terhadap Pertumbuhan Ekonomi di Indonesia - Kholidah Lidya Lubis; Lia Nazliana Nasution; Wahyu Indah Sari (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
In Indonesia economic growth is measured by Gross Domestic Product (GDP) and influenced by advancements in technology, infrastructure and innovation in the digital economy. This study analyzes the impact of digital transactions through e-commerce on economic growth, using indicators such as e-money, inflation, internet users,money supply, e-commerce users and transaction volume.The quantitive method employs time series data from 2014-2024 from the world Bank, Central statistics agency and bank Indonesia. The Two Stage Least Square (TSLS).which shows that transaction volume has significant positive effect on e-money. while the number of internet users and the money suplly have a positive but insignificant effect.E-money has a significant positive effect on economic growh,while the number of e-commerce users has a significant negative effect and inflation has a positive significant effect on economic growth. Strategiesfor services innovation and infrastructure development are needed to support the digital economy.